2005
DOI: 10.1038/sj.onc.1208654
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphorylation of paxillin affects the metastatic potential of human osteosarcoma

Abstract: To acquire information on signal alteration corresponding to the changes in metastatic potential, we analysed protein tyrosine phosphorylation of low-and high-metastatic human osteosarcoma HuO9 sublines, which were recently established as the first metastatic model of human osteosarcoma. Tyrosine phosphorylation of proteins around 60, 70, and 120-130 kDa was enhanced in highmetastatic sublines. Among these proteins, the protein around 70 kDa, which was most remarkably phosphorylated, was identified as paxillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 33 publications
5
72
1
Order By: Relevance
“…In the present study, PP2 and KI-Src inhibited VSMC migration, indicating that Src kinase activity mediates VSMC migration. Nifedipine potently inhibited PDGF-induced Src activation and tyrosine phosphorylation of Cas, paxillin, and cortactin, all of which have been implicated in cell migration [16][17][18] . Indeed, Kyaw and colleagues reported that Cas is involved in Anginduced VSMC migration 23) , and we previously used RNA interference techniques to demonstrate that Cas, cortactin, and paxillin are required for VSMC migration (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, PP2 and KI-Src inhibited VSMC migration, indicating that Src kinase activity mediates VSMC migration. Nifedipine potently inhibited PDGF-induced Src activation and tyrosine phosphorylation of Cas, paxillin, and cortactin, all of which have been implicated in cell migration [16][17][18] . Indeed, Kyaw and colleagues reported that Cas is involved in Anginduced VSMC migration 23) , and we previously used RNA interference techniques to demonstrate that Cas, cortactin, and paxillin are required for VSMC migration (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Src phosphorylates several actin-associated proteins, such as Cas, paxillin, and cortactin 14,15) . Tyrosine phosphorylation of these proteins has been reported to be involved in cell migration [16][17][18] . PDGF increased tyrosine phosphorylation of Cas, paxillin, and cortactin, and nifedipine significantly inhibited PDGF-induced phosphorylation of these proteins (Fig.…”
Section: Effect Of Nifedipine On Pdgf-induced Src Activation and Tyromentioning
confidence: 99%
“…These findings suggest that enhanced activity of SFKs and overexpression of paxillin synergistically contribute to the high metastatic potential of human osteosarcoma through the hyperphosphorylation of paxillin. 45 The relationships between paxillin expression and clinicopathological features including metastasis have been investigated in salivary adenoid cystic carcinoma (SACC). High expression of paxillin, in 57.45% of SACC as cytoplasmic staining, was correlated with a more advanced stage and metastasis in SACC, suggesting that paxillin may be a valuable biomarker in advanced SACC and SACC with distant metastasis.…”
Section: Involvement Of Paxillin In Tumor Metastasismentioning
confidence: 99%
“…The cell migration assay was performed as previously described [14]. Briefly, the number of HuH7 cells migrating through a polyethylene terephthalate (PET) filter with 8-”m pores (Beckton Dickinson, Franklin Lake, NJ, USA) in 24 h was counted under microscopic examination.…”
Section: Cell Migration Assaymentioning
confidence: 99%